Brief Report: Risk of Childhood Rheumatic and Nonrheumatic Autoimmune Diseases in Children Born to Women With Systemic Lupus Erythematosus. Issue 11 (26th October 2018) - Couture, Julie; Bernatsky, Sasha; Scott, Susan; Pineau, Christian A.; Vinet, Evelyne
Abstract : Objective: Several autoimmune diseases have familial aggregation and, possibly, common genetic predispositions. In a large population‐based study, we evaluated whether children born to mothers with systemic lupus erythematosus (SLE) have an increased risk of rheumatic and nonrheumatic autoimmune diseases versus children born to mothers without SLE. Methods: Using the Offspring of SLE Mothers Registry, we identified children born live to SLE mothers and their matched controls, and ascertained autoimmune diseases based on ≥1 hospitalization or ≥2 physician visits with a relevant diagnostic code. We adjusted for maternal age, education, race/ethnicity, obstetric complications, calendar birth year, and sex of child. Results: A total of 509 women with SLE had 719 children, while 5, 824 matched controls had 8, 493 children. The mean ± SD follow‐up period was 9.1 ± 5.8 years. Children born to mothers with SLE had a similar frequency of rheumatic autoimmune diagnoses (0.14%; 95% confidence interval [95% CI] 0.01–0.90) versus controls (0.19% [95% CI 0.11–0.32]). There was a trend toward more nonrheumatic autoimmune diseases in SLE offspring (1.11% [95% CI 0.52–2.27]) versus controls (0.48% [95% CI 0.35–0.66]). In multivariate analyses, we did not see a clear increase in rheumatic autoimmune disease (odds ratio [OR] 0.71 [95% CI 0.11–4.82]), but children born to mothers with SLE had a substantially increased risk of nonrheumatic autoimmune disease versus controls (OR 2.30 [95% CI 1.06–5.03]). Conclusion: Although the vast majority of offspring have no autoimmune disease, children born to women with SLE may have an increased risk of nonrheumatic autoimmune diseases versus controls. Additional studies assessing offspring through to adulthood would be additionally enlightening.